ฤทธิ์ขับปัสสาวะของชากระเจี๊ยบและหญ้าหวานเทียบกับยาไฮโดรคลอโรไทอะไซด์ในผู้ป่วยเบาหวานที่มีภาวะความดันโลหิตสูงในโรงพยาบาลจุฬาลงกรณ์ - ศศิธร แสงเนตร (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Objectives: To compare diuretic and antihypertensive effects of Roselle-Stevia (R-S) tea with hydrochlorothiazide (HCTZ) in diabetic patients with hypertension. Methods: This study was a prospective, randomized, open label, two-way crossover study. Twenty two diabetic patients with hypertension were randomly assigned with concealed allocation to receive either R-S tea (each sachet 2/0.2 g) 2 sachets daily or HCTZ 25 mg once daily for 30 days. Then there was a 7-day washout period followed by crossover to the other treatment. Diuretic effects (24-hour urinary sodium excretion and urine volume) and antihypertensive effects (home blood pressure monitoring) were assessed at the end of each 30-day treatment period.Results: Compared with baseline, both treatments slightly reduced 24-hour urinary sodium excretion (R-S tea from 157.1±87.5 to 151.8±58.5 mEq, p>0.05; HCTZ to 135.9±88.1 mEq, p>0.05) and urine volume (R-S tea from 1,709.5±935.6 to 1,608.2±721.7 mL, p>0.05; HCTZ to 1,669.1±732.8 mL, p>0.05). No significant difference was found in urinary sodium excretion and urine volume for R-S tea versus HCTZ (p > 0.05). We found that both R-S tea and HCTZ significantly reduced systolic/diastolic blood pressures from baseline (R-S tea from 144.5±7.6/81.3±8.9 to 139.2±9.8/78.5, p<0.05; HCTZ to 129.0±10.9/74.4±8.5 mmHg, p<0.05). The blood pressure reduction after R-S tea administration was -5.2±8.6/-2.8±8.6 mmHg, significantly less than after HCTZ (-15.5±9.1/-6.9±5.7 mmHg; p<0.05). No patient dropped out due to adverse events. Conclusions: Neither R-S tea nor HCTZ showed diuretic effect at 30th day of treatment in diabetic patients with hypertension. R-S tea decrease blood pressure less than HCTZ in hypertensive diabetic patients. Our findings suggest other mechanisms of action for the blood pressure lowering effect of R-S tea and HCTZ.